Praticas comunicativas de influenciadoras digitais no Instagram: mediações de autenticidade, visibilidade e algoritmos em narrativas digitais - Rinaldi, Matheus Baldo (Universidade Federal de São Carlos, 2025)
This study starts from the centrality and ubiquity of digital influencers in contemporary social media and seeks to understand how an exemplary sample of small-scale content creators constructs and mobilizes communicative practices aimed at the performance of authenticity and the generation of visibility on Instagram. Based on a qualitative approach anchored in a short-term ethnography adapted to digital environments, the publications shared on three selected profiles were analyzed through non-participant observation (the lurker method). The study articulates debates on authenticity, self-promotion, and the algorithmic norm that structures visibility mechanisms on the Internet. It was observed that the influencers employ dichotomous strategies: on one hand, they build proximity and affective bonds with their audiences; on the other hand, they reinforce distance and aspirational standards that sustain their credibility. The results indicate that authenticity, far from being an inherent characteristic, is configured as a social and commercial strategy, mobilized to consolidate lifestyles and foster consumption practices.
Communicative practices of digital influencers on instagram: mediations of authenticity, visibility, and algorithms in digital narratives
Keywords: Redes sociais; Instagram; Influenciadores digitais; Visibilidade; Autenticidade; Social networks; Digital influencers; Visibility; Authenticity.; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS; 12. Consumo e Produção Responsáveis